How does CEO power and overconfidence affect the systemic risk of China’s financial institutions? - Chen, Yingying; Safi, Adnan; Zeb, Yasir (Frontiers in Psychology, 2022)
The purpose of this paper is two-fold. First, this study measures the contribution of banks and non-bank financial institutions towards the systemic risk of China. Second, the present study investigates the relationship between CEO power, CEO overconfidence, and systemic risk. This study uses Delta Conditional Value-at-Risk (∆CoVaR) method to measure the systemic risk contribution of firms listed on the Shenzhen and Shanghai stock exchanges over a period of 2006-2018. The results show that non-bank financial institutions are systemically more important compared to banks. We employed fixed effects regression analysis to show that banks with overconfident CEOs increase the firm's systemic risk. The results also confirm that powerful CEOs enhance the contribution of non-bank financial institutions to systemic risk, whereas CEO power's impact was significant only for non-state-owned banks. The robustness test results obtained using the two-stage least squares method also further verify the results. These findings are important for constructing regulations to reduce the contribution of firms to systemic risk.